The Effectiveness of α-Mangostin in Reducing the Streptococcus Mutans Biofilm Thickness - Rahmawati Sri Praptiningsih; Arlina Nurhapsari; Rifqi Wahyu Febrian (Universitas Muhammadiyah Yogyakarta, 2022)
Dental caries occurs due to the demineralization of tooth structure caused by microorganisms in colonies called biofilms. One of the microorganisms involved in dental caries is Streptococcus mutans. Oral mouthwash, in addition to mechanical cleaning, is known to prevent the growth of oral microorganisms. Mangosteen is known as an anti-cancer ingredient with high anti-bacterial properties. This study aims to identify the effectiveness of mangosteen skin extract (Garcinia mangostana L.) in decreasing Streptococcus mutans biofilm. The study is experimental research with a post-test control group design. The research sample was divided into five groups; 3 treatment groups and 2 control groups. The biofilm thickness test was carried out with OD (Optical density) with a wavelength of about 620 nm using an ELISA reader. Kruskal Wallis analysis was employed as a non-parametric statistical test analysis. Statistical Kruskal Wallis indicated significant differences in the thickness of 5 test groups of Streptococcus mutans. The lowest average yield of biofilm thickness was in the α-mangosteen group at 12.5 g/ml. Conclusion: α-mangosteen in mangosteen skin extract effectively reduced the thickness of Streptococcus mutans biofilm.